(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The complex phonetic and expressive quality of Turkic languages makes the study of imitative words—also referred to as onomatopoeic and sound-symbolic words—an important area of research in Turkology. This study offers a thorough historical account of the investigation of imitative terms in the context of Turkic linguistics, from its inception to the present. Beginning with Mahmud al-Kashgari’s epic "Divan-i Lughat al-Turk," the study explores the first references to and classifications of imitative terms in ancient Turkic writings and dictionaries. This is where sound-symbolic aspects were first documented in an organised linguistic framework. We also go into great depth about later developments throughout the Soviet era and the post-independence period, showing how methodological methods changed from comparative and descriptive philology to structuralism and then to functional and cognitive paradigms. The research also charts how Turkological studies have been influenced by Western linguistic ideas, namely in the areas of morpho-phonological structure analysis, phonosemantics analysis, and semantic classifications of imitative terms. The annotation highlights how imitative words, which are ingrained in children’s language, oral traditions, and folklore, represent the naturalistic viewpoint and cultural distinctiveness of Turkic peoples. Particular focus is placed on how these words contribute to the lexicon’s enrichment, particularly in areas pertaining to nature, emotion, movement, and sound. Uzbek, Kazakh, Kyrgyz, Tuvan, and Turkish are only a few of the Turkic languages that provide comparative examples that highlight the variety and systematic patterns of sound imitation throughout the Turkic linguistic family. This book advances our knowledge of the ways in which scholars from various eras have examined these occurrences and how sound and meaning are perceived in Turkic languages. It also initiates a conversation on the difficulties in standardising and classifying imitative terms because of their context-dependence and flexibility. Overall, this study provides a thorough historiographical map of a sometimes disregarded yet linguistically rich aspect of the Turkic languages, making it an invaluable tool for linguists, philologists, and Turkology academics.